2015
DOI: 10.1682/jrrd.2015.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Student Veteran perceptions of facilitators and barriers to achieving academic goals

Abstract: Abstract-According to recent estimates, over 1 million Operation Iraqi Freedom/Operation Enduring Freedom Veterans are utilizing the post-9/11 GI Bill to pursue higher education. Data collected by the Department of Defense suggests that greater than 17% of returning Veterans may experience mental and physical health disorders, which can negatively affect school performance. The current study explored student Veterans' perceived facilitators and barriers to achieving academic goals. Thirty-one student Veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
0
40
1
Order By: Relevance
“…Both study populations (staff and faculty members) reported a lack of training about the student veteran population, 72.8% reported that there is no faculty training provided and 69.3% marked that there is no staff training on student veterans. Training for staff and faculty on the military culture could help them to understand student veterans' skills and strengths that can benefit the academic environment (Norman, et al, 2015). Staff and faculty identified that there is a lack of sensitivity for student veterans on campus (46.5%).…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both study populations (staff and faculty members) reported a lack of training about the student veteran population, 72.8% reported that there is no faculty training provided and 69.3% marked that there is no staff training on student veterans. Training for staff and faculty on the military culture could help them to understand student veterans' skills and strengths that can benefit the academic environment (Norman, et al, 2015). Staff and faculty identified that there is a lack of sensitivity for student veterans on campus (46.5%).…”
Section: Barriersmentioning
confidence: 99%
“…Student veterans can feel a sense of alienation on campus due to the differences between higher education and the military culture (O'Herrin, 2011). In Norman, et al's (2015) qualitative study of 31 student veterans, one of the themes that emerged from the interviews was lack of support from staff and faculty. It was suggested that staff and faculty could take a training on the military culture to better understand the strengths and barriers that student veterans face.…”
Section: Introductionmentioning
confidence: 99%
“…They miss the camaraderie they experienced in the military; they feel like outsiders among the 18-22 year-old traditional campus population; and they sense that faculty does not understand them. In addition, those with a diagnosis of PTSD were found to experience a greater sense of alienation within the campus environment (Norman, Rosen, Himmerich, Myers, Davis, Browne, & Piland, 2015;Elliott, Gonzalez & Larsen, 2011). Difference in culture is not the only difficulty facing veterans transitioning to college; financial difficulties often add another layer of stress for student veterans.…”
Section: Introductionmentioning
confidence: 99%
“…While most are happy to have the financial support of the GI Bill, they may be unprepared to deal with the bureaucracy around the application process, and the unpredictable delays in receiving funds. Students may find themselves dropped from classes due to late payments, (Norman, et al, 2015) or assuming more out-of-pocket expenses than they can afford, leading to credit card debt (Griffin & Gilbert, 2015;Ackerman, DiRamio, & Garza Mitchell, 2009). Debt compounds stress related to transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation